MiT family translocation-associated renal cell carcinoma: A report of two cases in children - Sriranjan Mukherjee; Keya Basu; Kalyani S. Basu; Uttara Chatterjee (Indian Journal of Pathology and Microbiology)
Renal cell carcinoma is uncommon in children and must be distinguished from the more common Wilms’ tumor. Here, we present two cases of renal cell carcinoma in children both of whom presented with hematuria. Accurate diagnosis is essential in order to differentiate it from epithelial predominant Wilms’ tumor which has vastly different prognosis and treatment. Immunohistochemistry for TFE3 is useful in establishing the diagnosis.